Effect Of Bevacizumab On Growth Of Human Nasal Polyposis In Vitro; An Off-Label Use Of Anti-Angiogenic Agent For Nasal Polyposis Treatment - Nemati S; Keihanian F; Saeidinia A; Bakhshaei M (Dove Medical Press, 2019)
Shadman Nemati,1 Faeze Keihanian,2,3 Amin Saeidinia,4,5 Mahdi Bakhshaei6 1Rhino-sinus, Ear, and Skull Base Diseases Research Center, Guilan University of Medical Sciences, Rasht, Iran; 2Cardiology Department, Imam Reza & Ghaem Hospital, Faculty of Medicine, Mashhad University of Medical Sciences, Mashhad, Iran; 3Pharmaceutical Research Division, Booali Research Center, Mashhad University of Medical Sciences, Mashhad, Iran; 4Faculty of Medicine, Guilan University of Medical Sciences, Rasht, Iran; 5Pharmaceutical Research Division, Booali Research Center, Mashhad University of Medical Sciences, Mashhad, Iran; 6Faculty of Medicine, Ear, Nose and Throat Department, Mashhad University of Medical Sciences, Mashhad, IranCorrespondence: Amin SaeidiniaFaculty of Medicine, Mashhad University Complex, Azadi Square, Mashhad 9177948564, IranTel +98 511 9119451607Email saeidiniaa971@mums.ac.irIntroduction: Nasal polyposis (NP) is a frequent problem during adulthood. Treatment of NP is primarily based on drugs, such as oral or topical steroids and in some types, by surgery. Despite of available therapeutic options for NP, recurrence after polypectomy is found. Vascular endothelial growth factor (VEGF) is a known factor involved in NP. Bevacizumab is a monoclonal antibody, which acts against VEGF.Aim: Regarding the availability of bevacizumab and its use in ophthalmic off-label application, in this study, we hypothesized that it could be a choice of non-invasive treatment. The researchers aimed at evaluating the use of bevacizumab in vitro on the growth of NP.Materials and methods: In this experimental study, the researchers used eight non-allergic NP tissues from patients admitted for polypectomy clinic of Imam Reza Hospital, Mashhad. Tissues were cultured in DMEM medium based on standard protocols in the presence or absence of bevacizumab (10 to 250 μM) then incubated. The mean of the responses was reported. The level of VEGF and MTT test for NP epithelial cell viability were determined for each group. Data were analyzed using the SPSS software.Results: The researchers demonstrated that bevacizumab leads to a decrease in the level of VEGF (the most common cause of angiogenesis in NP) in media culture of NP, dose-dependently (P<0.001). The highest mean was related to the 10-μM group and the least mean was related to the 250-μM group. In MTT test after 5 days, it was shown that the percentage of viable epithelial NP cells (due to apoptosis) was decreased dose-dependently and could lead to resolving NP tissue (P<0.001), significantly.Conclusion: This study showed that bevacizumab could help decrease the growth of NP tissue dose-dependently in organ culture in vitro by inhibiting VEGF. It seems that bevacizumab could be a good candidate for the treatment of non-allergic NP.Keywords: nasal polyposis, non-allergic polyps, bevacizumab, Avastin, in vitro study